Sharia Compliance,Internal Audit & Risk Management Function in IB - Al Rasyied, Muhammad Harun; Fatwa, Nur (UI Scholars Hub, 2025)
The new regulations from Otoritas Jasa Keuangan (OJK) of POJK No. 2/2024 and SEOJK No. 15/2024 require Islamic banks to support sharia compliance supervision by assigning three functions; Sharia Compliance, Sharia Internal Audit, and Sharia Risk Management. Therefore, the role of these three functions is an essential factor for Islamic banks in maintaining and mitigating the level of sharia compliance risk. This study aims to assess the effectiveness of supervision carried out by the three functions which are assessed from three attributes; namely Competence, Work Program, and Independence. The research data was obtained using a questionnaire method distributed to 10 islamic banks in Indonesia in 2025. The data then processed using SPSS software. The regression results show that the three attributes have a positive yet insignificant effect on the level of sharia compliance. This shows that in the adjustment phase with this new regulation, these three functions must have better competence, work programs, and independence in order to play a more effective role in supervising sharia compliance risks.